Peripheral blood lipid and liver and kidney function test results in long-term night shift nurses: a cross-sectional study in South China - Zhao, Yang; Lu, Xunhao; Wang, Yanghua; Cheng, Yiyi; He, Qiao; Qin, Rongqi; Li, Wenrui; Liu, Haizhou; Liu, Yuanfang (Frontiers in Endocrinology, 2023)
Purpose: This study aimed to elucidate the effects of long-term day and night shifts on liver function and lipid metabolism in a group of nurses.This cross-sectional study in December 2019 was based on a group of nurses.One thousand two hundred fifty-three physically healthy caregivers were included, including 1231 women and 22 men. 886 nurses had long-term shift work(work (working in a rotating system for >1 year). The receiver operating characteristic (ROC) curve and Logistic regression analyses were used to evaluate factors related to longterm shift work.We observed differences in liver and kidney indicators between the non-night and night shift groups. The ROC curve revealed that CHO (AUC: 62.4%), LDLC (AUC: 62%), and GLUO (AUC: 61.5%) were more related to the night shift. Logistic regression analysis showed night shift work was associated significantly with CREA